Increase in Knowledge of Dental Health Using Animated Video - Tibertius A. W Dali; Ribka Limbu; Daniela L. A. Boeky (Lontar : Journal of Community Health, 2020)
Dental health problems are a very important concern in child development because of the vulnerability of school-age children to dental health problems. It happens because of problems with knowledge about dental health in children. This study aims to determine the increase in dental health knowledge using animated video media for health education in elementary school students in North Mollo. This is a pre-experimental design, with a one group pre-test and post-test design research design. This design does not have a comparison group, but at least a first observation (pre-test) has been made which allows testing of changes that occur after the experiment. The sampling technique used in this study was the purposive sampling technique, and the sample size is 51 students. The results of the analysis using the Wilcoxon statistical test showed that the animated video was effective to increase knowledge about dental health with a significance value (ρ) 0.00 <(α) 0.05. Animated video media can be used as an outreach technique about maintaining dental health in elementary school-aged children.